2013
DOI: 10.1159/000345929
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interaction between Losartan andRhodiola roseain Rabbits

Abstract: Aim: The study investigates the potential interaction of the herbal medicinal product of Rhodiola rosea on the pharmacokinetics of losartan and its active metabolite EXP3174 after concurrent oral administration to rabbits. Materials and Methods: We conducted a randomized, single-dose, two-treatment, two-period, two-sequence, cross-over pharmacokinetic study on 6 healthy female New Zealand rabbits, after concurrent oral administration of losartan (5 mg/kg) and the herbal medicinal product of R. rosea (50 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…A case report on a 68‐year‐old female patient with recurrent moderate depression developed serotonergic syndrome after taking R. rosea together with paroxetine, indicating a potential pharmacokinetic and dynamic interactions . Concurrent use of R. rosea significantly altered pharmacokinetic properties of losartan in rabbits . It is demonstrated that Rhodiola extracts and some of the constituents such as rhodiosin and rhodionin are potential inhibitors of cytochrome P450 enzymes and P‐gp transporter .…”
Section: Safety Issuementioning
confidence: 99%
“…A case report on a 68‐year‐old female patient with recurrent moderate depression developed serotonergic syndrome after taking R. rosea together with paroxetine, indicating a potential pharmacokinetic and dynamic interactions . Concurrent use of R. rosea significantly altered pharmacokinetic properties of losartan in rabbits . It is demonstrated that Rhodiola extracts and some of the constituents such as rhodiosin and rhodionin are potential inhibitors of cytochrome P450 enzymes and P‐gp transporter .…”
Section: Safety Issuementioning
confidence: 99%
“…In the study by Panossian et al (2009), no significant inhibition was found in the metabolism of warfarin and theophylline in rats following oral administration of R. rosea. Opposed to this, the study by Spanakis et al (2013), showed a significant inhibition in the metabolism of losartan [CYP3A4, CYP2C9 and CYP2C10 substrate (Sica et al 2005)] in rabbits after oral administration of a R. rosea product. Just recently, we found a 23% reduction in CYP2C9 activity in a cross-over study (including 13 human males) with the commercial R. rosea product Artic Root (Thu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Five studies have previously been published on CYP inhibition by full extracts of R. rosea (Scott et al 2006;Panossian et al 2009;Hellum et al 2010;Spanakis et al 2013;Thu et al 2016). Hellum et al (2010) showed that ethanol extracts of R. rosea clones (raw plant material) significantly inhibited CYP3A4 in vitro, with IC 50 values ranging from 1.7-3.1 lg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…(), who found an almost twofold increase in AUC of the CYP2C9 substrate losartan after a 50 mg/kg concurrent administration of a commercial R. rosea extract to six rabbits in a two‐way crossover study, concluding that R. rosea could be categorized as a moderate in vivo inhibitor and that a study in humans was needed. Recently, our group published a study evaluating CYP1A2, CYP2C9, CYP2C19, CYP2D6, and CYP3A4 interaction in man by a commercially available R. rosea product similar to that used by Spanakis et al (). In this study, using a two‐phase, randomized cross‐over cocktail study in 13 males, we found a 21% reduction in the EXP‐3174/losartan ratio, indicating a significant inhibition of CYP2C9 enzyme activity (Thu et al.…”
Section: Introductionmentioning
confidence: 99%